DNA from wood - A simple approach facing a challenging matrix - A preliminary study. (September 2020) - Paranaiba, Renato T.F.; Carvalho, Carlos B.V.; Paiva, Renata Silva; Trindade, Bruno Rodrigues; Barros, Marcelo Garcia; Souza, Elisa Palhares; Gontijo, Alexandre Bahia; Silveira, Dâmaris
Highlights: Plant DNA barcoding is a handy botanical identification tool applied to forensics. Wood is a challenging material once it demands effective DNA extraction methods. Cross-sections of trunks obtained from Aspidosperma sp. were used in a pilot study. A widely used semi-automated method was evaluated to forensic DNA extraction. A successful adaptation in a DNA extraction method is proposed for woody materials. Abstract: Plant DNA barcoding has proven to be a handy tool for identifying botanical species. However, extracting DNA from woody materials is often a challenging task. Forensic applications, therefore, must be able to overcome the technical difficulties of this nature. A simple and successful adaptation, through a widely used method in forensic laboratories, using chemistry based on magnetic DNA isolation technology and a robotic platform, is presented here. The model case was the application of this adapted DNA extraction method for the identification of Aspidosperma spp., a genus comprising several species in all biomes of Brazil, including Cerrado and Rain Forest. Such technology adaptation can aid in the identification of seized material and help in investigations involving illegal logging and deforestation, ultimately contributing to environmental protection.